Architecture, Devotion, and Power: The Kalasan Temple and Buddhist Legitimation under the Śailendra Dynasty - Tomy Wijaya; Fatimah Alauwiyah; Muhammad Reza Pahlevi (Universitas Gadjah Mada, 2025)
This study analyzes Kalasan Temple as a religious and political entity that articulated and mobilized Mahayana Buddhist ideology to bolster dynastic legitimacy during the Śailendra dynasty in eighth-century Java. The study utilizes a historical-archaeological approach, systematically applying heuristics, critical source evaluation, interpretation, and historiography to both primary data, specifically the Kalasan Inscription (778 CE) and the temple’s architectural and ornamental characteristics, as well as secondary scholarship in history, archaeology, and Buddhist studies. This research reinterprets epigraphic and architectural data by contextualizing Kalasan within the broader framework of contemporary Buddhist monuments in Central Java, such as Sari, Plaosan, and the Borobudur complex, to evaluate common ideological patterns and institutional strategies, rather than regarding existing literature as a descriptive authority. The analysis reveals that Kalasan’s establishment as a Bhavanam, bolstered by royal patronage and simā land grants, signifies a purposeful incorporation of Mahayana devotional practices into the political framework of Ancient Mataram. The study demonstrates, through comparative architectural and contextual analysis, that Mahayana Buddhism functioned as both elite religiosity and a legitimizing framework connecting rulers, monastic communities, and society. This article emphasizes methodological rigor and intersite comparison, offering critical insights into the interplay between religious ideology and political authority, demonstrating how sacred architecture actively influenced the development of early Javanese civilization.